Heavy Metal sensor based on chitosan biopolymer by electrodeposition method - Eljali, Ahmed Masaud S. (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
i- To fabricate a reliable sensor to detect heavy metal ion based on chitosan biopolymer. ii- To fabricate a heavy metal sensor through electrodeposition technique. iii- To study the electrical properties of heavy metal sensors upon different deposition time and metal concenttration. iv- To characterize the microstructure of chitosan bypolymer after annealing and deposition.